Analysis of the Implementation of BPJS Health Integrated Marketing Communication in Socializing the JKN Mobile Application in Jambi City in 2023 - Mukhdi, Fuad Ajrul; Noerjoedianto, Dwi; Amir, Andy (Journal of Midwifery and Nursing, 2024)
Based on data from BPJS Kesehatan Jambi Branch, Mobile JKN users in Jambi City are only 18.6% of all people registered as JKN members. This means that only 155,702 of the 622,014 JKN participants in Jambi City use the Mobile JKN application. The low use of mobile JKN is caused by low public awareness of the existence of this Mobile JKN application. Thus, it is necessary to have appropriate marketing activities to increase public awareness of the existence of this application. This study used a qualitative method with a descriptive approach involving 8 informants consisting of the head and members of the BPJS Health Socialization team Jambi Branch and Mobile JKN Users in Jambi City.  The main techniques in this research are observation and in-depth interviews. The purpose of this study was to determine how the implementation of integrated marketing communication carried out by BPJS Kesehatan Jambi Branch in socializing the Mobile JKN application in Jambi City. This study found that BPJS Kesehatan Jambi Branch has not fully carried out integrated marketing communication activities in socializing Mobile JKN in the Jambi City area. The integrated marketing activities that have been carried out include advertising, personal selling, and public relations activities. As for direct marketing activities, it is has been not running.